2012
DOI: 10.2478/v10086-012-0024-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth and diet of the pikeperch Sander lucioperca (L.) in two French reservoirs

Abstract: Abstract. The pikeperch Sander lucioperca (L.) is present in numerous French water bodies. However, few studies have focused on the biology and ecology of the species and, as a result, references are lacking to assess its adaptation to lacustrine environments. The growth and diet of pikeperch were investigated in two reservoirs located in southern France. The fish at both sites show similar growth rates to those reported in other European countries, but slower than those observed in the Camargue. It is faster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 16 publications
8
21
0
7
Order By: Relevance
“…A general pattern for the feeding habits of pikeperch was suggested by numerous authors (Kangur 2000;Keskinen & Marjomäki 2004;Kangur et al 2007), in which small individuals (young individuals of approximately under one year old) prey mainly on arthropods and while larger individuals feed on fishes. However, the shift to piscivory may occur later in environments with lacked forage fish (Argiller et al 2003). Ontogenetic change in feeding habits is an almost universal phenomenon in fishes and thus its occurrence in pikeperch is not surprising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A general pattern for the feeding habits of pikeperch was suggested by numerous authors (Kangur 2000;Keskinen & Marjomäki 2004;Kangur et al 2007), in which small individuals (young individuals of approximately under one year old) prey mainly on arthropods and while larger individuals feed on fishes. However, the shift to piscivory may occur later in environments with lacked forage fish (Argiller et al 2003). Ontogenetic change in feeding habits is an almost universal phenomenon in fishes and thus its occurrence in pikeperch is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Thus some studies have demonstrated that cannibalism is related with both the abundance of young-of-year and adult pikeperch (Frankiewicz et al 1999;Kangur 2000;Lappalainen et al 2006). The abundance of other prey is often suggested to affect the cannibalism of pikeperch (Campbell 1992;Argiller et al 2003). If other prey is very abundant, the degree of cannibalism should be lower as compared with the situation when other prey is rare and the probability of cannibalism is increased.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of the species to utilize different prey with equal success not only ensures its ability to colonize the Neretva River but also to position itself as the dominant species in the local food webs, outcompeting other endemic species. A similar feeding pattern was reported for pikeperch from Lake Võrtsjärv (Estonia), including cannibalism, forcing to extinction of one native species and shifting towards other small pelagics (Kangur et al ., ), and in two French reservoirs (Argillier et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Ze zijn dan ongeveer 4 maanden oud. In het eerste jaar zijn maximale lengtes genoteerd van 23 cm tot 42 cm in het tweede jaar (Argillier et al, 2003 …”
Section: Haringunclassified